2001
DOI: 10.1007/s001050170065
|View full text |Cite
|
Sign up to set email alerts
|

Die Reziprozitätsregel in der Photobiologie

Abstract: According to the rule of Bunsen and Roscoe, a photochemical reaction is directly proportional to the total energy dose, irrespective of the time over which this dose is delivered. To date few studies have addressed the validity of this rule in experimental and applied photobiology. Most of these data point to the fact that the rule of reciprocity is invalid or of limited validity for many photobiological reactions. For UV-induced cell death, photocarcinogenesis, psoralen photochemistry, and the effects of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In fact, if the number of photons is higher than this limit, the antimicrobial effect will decrease because the dye in suspension will not absorb all the excess light [160]. Schindl et al [161] referred that the biological effect of light depends on the fluence, irrespective of the time over which this dose is delivered. Maclean et al [162] also indicate that the inactivating light may be applied at high irradiance over a short time or at lower irradiance over a longer time.…”
Section: Factors Affecting Viral Pdimentioning
confidence: 99%
“…In fact, if the number of photons is higher than this limit, the antimicrobial effect will decrease because the dye in suspension will not absorb all the excess light [160]. Schindl et al [161] referred that the biological effect of light depends on the fluence, irrespective of the time over which this dose is delivered. Maclean et al [162] also indicate that the inactivating light may be applied at high irradiance over a short time or at lower irradiance over a longer time.…”
Section: Factors Affecting Viral Pdimentioning
confidence: 99%
“…Others studies demonstrate more viral inactivity at lower, compared with higher, fluence rates for the same total fluence (9, 12). Schindl et al (13) reported that the total photodynamic damage of light depends on the fluence, irrespective of the fluence rate. However, it is difficult to compare clinical results obtained using different photosensitizers, light sources and doses of light.…”
Section: Discussionmentioning
confidence: 99%
“…There is no reciprocity when a damage (e.g. of DNA) is produced (Schindl et al, 2001). Along with the mentioned, generally valid laws, there are a few rules and principles describing and explaining particular photochemical and photophysical processes.…”
Section: Down Of Photochemistry As a Sciencementioning
confidence: 99%